Human Rights Overboard: The Long Xing 629 Case and the Legality of Sea Burials in International Law - Ridwan Arifin; Sarah Rinda Sulistyoningrum; Izan Mateo Cassandro (Tirtayasa Journal of International Law, 2026)
The disposal of Indonesian crew members’ bodies by the Long Xing 629 exposed a harrowing gap in maritime labor protections and international human rights law. This study analyzes the legality of burials at sea against established international standards, examining whether such practices constitute a necessity or a convenient cover for rights abuses. Utilizing a normative juridical method with a statutory and international law approach, this research examines the legal implications of the disposal of Indonesian crew members’ bodies at sea by the Long Xing 629. The study analyzes the jurisdictional and enforcement gaps within the 1982 United Nations Convention on the Law of the Sea (UNCLOS), particularly concerning the obligations of flag states under Articles 94 and 98, the protection of human dignity at sea, and the accountability mechanisms for alleged human rights abuses against migrant fishery workers. Furthermore, the research evaluates whether burial at sea in this case constituted a legitimate maritime necessity under international maritime practice or served as a concealment of labor exploitation and violations of international human rights standards. While flag states—in this case, China—hold primary jurisdiction on the high seas, the Long Xing 629 incident reveals a blatant disregard for burial protocols and the fundamental dignity of migrant workers. The findings suggest that weak enforcement mechanisms allow flag states to bypass accountability, leaving Indonesian seafarers in a legal vacuum. The study concludes that the Indonesian government must pivot toward aggressive diplomatic and legal strategies to hold flag states liable for human rights violations, ensuring that the high seas do not remain a lawless zone for the global maritime workforce.